A Meta-Analysis of the Effects of Cross-Cutting Exposure on Political Participation. (2nd October 2019) - Matthes, Jörg; Knoll, Johannes; Valenzuela, Sebastián; Hopmann, David Nicolas; Von Sikorski, Christian
Abstract : Scholars have advanced many theoretical explanations for expecting a negative or positive relationship between individuals' cross-cutting exposure—either through interpersonal or mediated forms of communication—and their political participation. However, whether cross-cutting exposure is a positive or negative predictor of participation is still an unsettled question. To help fill this gap, we conducted a meta-analysis of 48 empirical studies comprising more than 70, 000 participants examining the association between cross-cutting exposure and political participation. The meta-analysis produced two main findings. First, it shows that, over all studies, there is no significant relationship, r = .002, Zr = .002 (95% CI = −.04 to .05). Second, the null relationship cannot be explained by variations in the characteristics of cross-cutting environments (e.g., topic, place, or source of exposure), participation outcomes (e.g., online vs. offline activities), or methods employed (e.g., experiment vs. survey). Taken together, these results should alleviate concerns about negative effects of cross-cutting exposure on political engagement. Implications for future research are discussed.